A curtailed selection and testing design for comparing binomial treatments with a standard - Buzaianu, Elena; Razaila, Luminita (Sequential analysis, 2025)
In this article we use strong curtailment to define a hybrid selection and testing procedure for comparing success rates of several populations among each other and against a desired standard success rate. Our curtailment procedure is based on the fixed-sample-size selection and testing procedure proposed by Schmidt and Buzaianu ( 2022 ). The proposed procedure satisfies the same probability requirements as the original procedure but requires fewer observations.